1981
DOI: 10.1177/002224298104500211
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Product Characteristics on the Export Performance of New Industrial Products

Abstract: New products tend to achieve better than average export sales. But all new products are not exportable, so managers face a problem in deciding which new products to emphasize. This study of 82 Canadian industrial goods firms shows that relative advantage is not the only characteristic to consider in judging a new product's export potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…Using a sample of 233 US firms they found that export pricing, and going directly to the buyer had the biggest impact on export performance. McGuinness and Little (1981) examined the influence of product and firm characteristics on exporting of new products, whereas Samiee and Walters (1990) examined only firm characteristics such as size on both export planning and performance. McGuinness and Little found that certain product characteristics had an impact on export performance, but that firm characteristics were more important.…”
Section: International Business Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a sample of 233 US firms they found that export pricing, and going directly to the buyer had the biggest impact on export performance. McGuinness and Little (1981) examined the influence of product and firm characteristics on exporting of new products, whereas Samiee and Walters (1990) examined only firm characteristics such as size on both export planning and performance. McGuinness and Little found that certain product characteristics had an impact on export performance, but that firm characteristics were more important.…”
Section: International Business Marketingmentioning
confidence: 99%
“…How firms integrate customer requirements into the product design process was the subject of a small sample (12) study by Bailetti and Litua (1995). McGuinness (1990) and Rochford (1991) examine new product idea generation and screening, the latter using a small response set of twenty-nine high technology firms.…”
Section: New Product Development and Diffusionmentioning
confidence: 99%
“…Since then, the scope of the discussion has expanded to include the entire marketing programme (Buzzell, 1968) and marketing process (Sorenson and Wiechmann, 1975). Among the elements of the marketing programme, the product and advertising variables have received most of the research attention in the literature (Hill and Still, 1984;Jain, 1989;Keegan, 1969;Levitt, 1983;McGuinness and Little, 1981;Walters and Toyne, 1989). Standardization has been conceptualized in different ways.…”
Section: A Brief Review Of the Standardization Literaturementioning
confidence: 99%
“…However, advertising, exhibitions, foreign language proficiency, and use of Government export services did not appear as the most important factors in successful exporting. McGuinness and Little (1981) concluded that new products tend to achieve better than average export sales. Kirpalani and Macintosh (1980) found that pricing and promotion were significantly associated with the firm's export performance, but distribution (quality and compensation of dealers and adequacy of stocks and parts) was not related to success.…”
mentioning
confidence: 99%